2017
DOI: 10.1093/ntr/ntx163
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Postpartum Return to Smoking: A Systematic Review

Abstract: This is the first systematic review of factors that may facilitate or inhibit PPRS. Considering how having a partner or household member who smokes, intending to quit smoking only for pregnancy, having self-efficacy to quit long term, breastfeeding and depression exert direct or indirect impacts on women's relapse to smoking and how such impacts could successfully be manipulated will inform development of new interventions to prevent PPRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
61
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 65 publications
13
61
2
Order By: Relevance
“…Finally, women who did (vs. did not) relapse postpartum were nearly twice as likely to have a partner who continued smoking postpartum. These findings are consistent with prior studies [24,25,27,32,37] and provide more insight into the relationship between the timing of the partner's smoking behavior and maternal smoking status around pregnancy (e.g., women who smoked during the entire pregnancy were nearly 4.5 times more likely to have a partner who decreased their smoking or quit smoking during pregnancy compared to women who did not smoke during the entire pregnancy).…”
Section: Discussion/conclusionsupporting
confidence: 90%
“…Finally, women who did (vs. did not) relapse postpartum were nearly twice as likely to have a partner who continued smoking postpartum. These findings are consistent with prior studies [24,25,27,32,37] and provide more insight into the relationship between the timing of the partner's smoking behavior and maternal smoking status around pregnancy (e.g., women who smoked during the entire pregnancy were nearly 4.5 times more likely to have a partner who decreased their smoking or quit smoking during pregnancy compared to women who did not smoke during the entire pregnancy).…”
Section: Discussion/conclusionsupporting
confidence: 90%
“…Pregnant and postpartum smokers tend to be of a lower socioeconomic status, less well educated and have lower levels of support ( Chamberlain et al, 2017 ; Orton et al, 2018 ). Future interventions and their BCT components need to be tailored to address the specific needs and cultural identity of these high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Randomised controlled trials published prior to 2015 were identified by handsearching Jones ( Jones et al, 2016 ) and other recent pertinent systematic reviews of smoking cessation in pregnancy ( Chamberlain et al, 2017 ; Coleman et al, 2015 ) and postpartum relapse prevention interventions ( Notley et al, 2015 ; Orton et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations